STATISTICS AND RELIGION IN MODERN RUSSIA - Olga A. Mahova; Mikhail V. Karmanov (Статистика и экономика, 2016)
The statistics historically is the recognizedtool characteristics of social phenomenaand processes. However, for a number of objective reasons, statistical informationon the status and development of religioncauses contradictory assessments. In thisregard features and problems of interactionof statistics and religion in modern societyrepresent keen interest.